Design of Structural Concrete with Bone China Fine Aggregate Using Statistical Approach - Chandra Prakash Gour; Priyanka Dhurvey; Nagaraju Shaik (Advances in Materials Science and Engineering)
In this rapidly industrializing world, recycling materials for construction is crucial for protecting natural resources and promoting sustainable human growth. It should be carefully considered because using the waste in the structural concrete is cost-effective but it is also constrained due to its declining qualities. Bone China waste (BCW) possesses pozzolanic properties and it was occasionally used in concrete by a few researchers. Therefore, in the current investigation, the workability, compressive, split tensile, and flexure strengths of the fresh and hardened characteristics are first determined. 0%, 20%, 40%, 60%, 80%, and 100 percent of (BCW) were utilized to replace natural fine aggregate (sand). The experiment’s findings demonstrate that every percentage of BCW replacement yields the desired characteristic strength, a mix with 60% BCW yielding the highest strength value. Furthermore, it was discovered that utilizing fine bone China instead of conventional fine aggregate in concrete increased the compressive, split tensile, and flexure strength. Through traditional laboratory experiments, a valid criterion for choosing an ideal mix combination of BCW as fine aggregate in concrete is quite laborious and time-consuming. As a result, the statistical models were presented based on the laboratory-tested compressive strength data for concrete including varying amounts of bone China waste as fine aggregate, which show resilience and normality when assessed using fundamental statistical techniques. Finally, a good agreement was found between the created models and the experimental results as well as with proven existing models. These models can forecast the compressive, flexural, and split tensile strengths of concrete when combined with bone China fine aggregates or any other type of fine waste. With this framework, one may examine the same factors as the study and make sure that concrete has the maximum strength and sustainability. An improved microstructure of the concrete was observed which exhibits fewer porosity and cracks when fine BCW was used in place of sand.